Neoliberally framed suffering in professionals and patients in palliative care settings – 'telling cases' from an ethnographic multi-sited field study in Denmark. - Glasdam, Stinne; Boelsbjerg, Hanne Bess; Stjernswärd, Sigrid (Mortality, 2024)
In western countries, palliative care is a part of the formal healthcare system, ruled by neoliberal, organisational ideas. This Danish study illuminates how nurses and patients with non-western immigrant backgrounds (inter)act in relation to encounters in palliative care settings. Two 'telling' cases were selected, based on interviews and participating observations from a multi-sited ethnographic field study in Denmark. The results showed different care consequences of the structural framework, referring to, for example, political healthcare logics, strategies, and priorities, and illuminated how neoliberally organised healthcare systems inflicted suffering on patients and frustration amongst professionals. It did not seem that the immigrant background per se induced the challenges. The understandings of care and treatment conflicted as nurses often represented a medical, neoliberal logic of disease, treatment, and care, and patients often represented a non-medical logic of disease, formed by their lives. When palliative care took place in a general setting, (inter)actions were also influenced by a curative agenda of treatment and care. The study added to the evidence of the power of neo-liberal rationality across different forms of care and populations, regardless of ethnicity or location of that care.